Contact and bending load capacity enhancement through high entropy alloys. (October 2019) - Rajesh, S.; Marimuthu, P.; Dinesh Babu, P.
Abstract: The present work attempts to study the load carrying capacity of normal contact ratio spur gear by high strength less weight materials. In this study, High Entropy Alloys (HEA) AlCrFeNiMo0.5, Al80 Li5 Mg5 Zn5 Cu5, Al7075-T6, and Ti-6Al-4V are considered and have high stiffness with high strength to weight ratio compared to conventional steel used for gear. The bending and contact load capacity of each material is determined through finite element analysis and validated analytically. The contact and bending stresses are determined for the selected materials. It has less induced stress and load carrying capability enhancement of symmetric spur gear compared with an EN24 steel gear. The numerical result shows that the contact stress determined for Al80 Li5 Mg5 Zn5 Cu5 (HEA) and Al7075-T6 alloy gear is less compared to EN 24 steel gear. Hence, high strength to weight ratio is achieved by using high entropy alloys.